Honoring the teaching profession: the untold story of oppression and dissatisfaction of Technical and Vocational Education and Training (TVET) instructors - Omar, Muhd Khaizer; Mat Rashid, Abdullah; Mohd Puad, Mohd Hazwan; Nor Azman, Ady Hameme (Universidad Autonoma de Ciudad Juarez, 2019)
Currently, Technical and Vocational Education and Training (TVET) is one of the most discussed educational fields. In fact, TVET has been included in the nation’s budget especially for the development of facility and policy making. Notably, TVET has recently underlined the significance of teachers’ preparation program with regards to the issue of teaching job dissatisfaction. Purposefully, a mixed-method design was employed by adopting a convergent parallel design where both qualitative and quantitative data were combined in a single instrument. Results from the narrative interpretation were derived from the open-ended qualitative questions. In particular, Qualtrics, an online-survey form was utilized to collect the research data. For this study, the target population comprised of Malaysian training instructors at TVET educational institutions. Next, a thematic analysis was employed using the Atlas.ti software to determine the TVET instructors’ dissatisfaction factors. Accordingly, six themes were highlighted: burdened with administrative tasks, forced to manipulate students’ achievement documentations, improper planning of TVET programme implementation, student factor, inconducive working environment, and unstable TVET system. Although it was hard to grasp the essence of the existing scenario, it is strongly believed that the findings will spark much interest from the educational stakeholders, especially at the TVET division level to modify the current policy and plan a comprehensive teachers’ preparation program. Primarily, the findings of this study are objectively constructive to motivate TVET instructors towards creating a positive image of teaching, besides discarding any negative conceptions or misaligned goals, especially in the TVET field.